Effect of Monoclonal Antibody Blockade of Long Fragment Neurotensin on Weight Loss, Behavior, and Metabolic Traits After High-Fat Diet Induced Obesity - Wu, Zherui; Stadler, Nicolas; Abbaci, Amazigh; Liu, Jin; Boullier, Agnès; Marie, Nicolas; Biondi, Olivier; Moldes, Marthe; Morichon, Romain; Feve, Bruno; Melander, Olle; Forgez, Patricia (Frontiers in Endocrinology, 2021)
Background: Obesity is a major public health problem of our time as A risk factor for cardiometabolic disease and the available pharmacological tools needed to tackle the obesity pandemic are insufficient. Neurotensin (NTS) is a 13 amino acid peptide, which is derived from a larger precursor hormone called proneurotensin or Long Form NTS (LF NTS). NTS modulates neuro-transmitter release in the central system nervous, and facilitates intestinal fat absorption in the gastrointestinal tract. Mice lacking LF NTS are protected from high fat diet (HFD) induced obesity, hepatic steatosis and glucose intolerance. In humans, increased levels of LF NTS strongly and independently predict the development of obesity, diabetes mellitus, cardiovascular disease and mortality. With the perspective to develop therapeutic tools to neutralize LF NTS, we developed a monoclonal antibody, specifically inhibiting the function of the LF NTS (LF NTS mAb). This antibody was tested for the effects on body weight, metabolic parameters and behavior in mice made obese by high-fat diet. Methods: C57bl/6j mice were subjected to high-fat diet (HFD) until they reached an obesity state, then food was switched to chow. Mice were treated with either PBS (control therapy) or LF NTS mAb at the dose of 5 mg/kg once a week (i.v.). Mice weight, plasma biochemical analysis, fat and muscle size and distribution and behavioral tests were performed during the losing weight period and the stabilization period. Results: Obese mice treated with the LF NTS mAb lost weight significantly faster than the control treated group. LF NTS mAb treatment also resulted in smaller fat depots, increased fecal cholesterol excretion, reduced liver fat and larger muscle fiber size. Moreover, mice on active therapy were also less stressed, more curious and more active, providing a possible explanation to their weight loss. Conclusion: Our results demonstrate that in mice subjected to HFD-induced obesity, a blockade of LF NTS with a monoclonal antibody results in reduced body weight, adipocyte volume and increased muscle fiber size, possibly explained by beneficial effects on behavior. The underlying mechanisms as well as any future role of LF NTS mAb as an anti-obesity agent warrants further studies.